Atomic-Force Microscopy and Its Applications 2019
DOI: 10.5772/intechopen.77204
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Potential of Atomic Force Microscopy with Special Focus on Age Determination of Bloodstains

Abstract: An important aspect of any crime scene investigation is to detect, secure and analyze trace evidence. In forensic examinations where topographic characterization is important like in fingermark, textile and document forgery examinations, the atomic force microscopy (AFM) imaging technique can be of value. However, it is the force spectroscopy that could make AFM a versatile tool in crime investigations. Particularly, the ability to measure changes in mechanical properties of forensic trace material over time m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…An additional information to consider is that the indentation process is a crucial aspect of accurately determining RBCs Young Modulus parameters by AFM. As reported by Smijs et al [54] the material from which the used cantilever is made does influence the measurements, especially as the stiffness of erythrocytes increases over time.…”
Section: Transfusions and Further Prospectsmentioning
confidence: 89%
“…An additional information to consider is that the indentation process is a crucial aspect of accurately determining RBCs Young Modulus parameters by AFM. As reported by Smijs et al [54] the material from which the used cantilever is made does influence the measurements, especially as the stiffness of erythrocytes increases over time.…”
Section: Transfusions and Further Prospectsmentioning
confidence: 89%
“…They found that a bloodstain age determination with a 24 h precision only for 6-7 day old stains can be done. The silicon tip condition was regularly checked using scanning electron microscopy as an increase in bluntness was noticed after four to six cell indentations [28].…”
Section: Morphological Comparison Of Rbcs On Mica (A) and Glass (C) A...mentioning
confidence: 99%